16th MyPSA NPSC 2023 showcases sportsmanship and networking / Sofia Umaira Ismail, Muhammad ‘Izzuddin Zamery and Dr. Gurmeet Kaur Surindar Singh - Ismail, Sofia Umaira; Zamery, Muhammad ‘Izzuddin; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
The 16th Malaysian Pharmacy Students’ Association (MyPSA) National Pharmacy Sports Carnival (NPSC) 2023 was successfully held from March 17th to 19th at the main campus of Universiti Sains Malaysia (USM), Penang. The event was organised by Persatuan Sains Farmasi (PSF), USM, in collaboration with the Malaysian Pharmacy Students’ Association (MyPSA), with the aim of bringing back the spirit of healthy competition among participants and regaining their enthusiasm for sports after two years of online activities due to the pandemic crisis. The event saw the participation of 20 universities from across Malaysia. UiTM was one of the universities that participated in the carnival, with a contingent of 53 students from all four current batches.